2001
DOI: 10.2307/2657036
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level variation in the expression of heterostyly in three species of Rubiaceae: does reciprocal placement of anthers and stigmas characterize heterostyly?

Abstract: Heterostyly (i.e., reciprocal placement of anthers and stigmas between two or three floral morphs) is hypothesized to enhance outcrossing and reduce selfing. However, few studies have documented reciprocity among individual plants; instead, mean anther and stigma heights for floral morphs are usually reported, masking interindividual variation. We measured eight floral dimensions for individuals in five populations of three heterostylous Rubiaceae. The three methods used to quantify reciprocity yielded differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
20

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(131 citation statements)
references
References 43 publications
(92 reference statements)
8
101
0
20
Order By: Relevance
“…Such studies took into consideration a great number of individuals from a number of populations and revealed that variation of floral traits associated with distyly may exhibit overlapping of values. Pailler & Thompson (1997) and Faivre & McDade (2001) found variations among flowers of the same individual, among individuals of the same population and among populations of the same species. As pointed out by Barrett & Shore (1987), investigation in floral trait variation among populations may provide important information about the evolution, maintenance and/or loss of heterostyly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies took into consideration a great number of individuals from a number of populations and revealed that variation of floral traits associated with distyly may exhibit overlapping of values. Pailler & Thompson (1997) and Faivre & McDade (2001) found variations among flowers of the same individual, among individuals of the same population and among populations of the same species. As pointed out by Barrett & Shore (1987), investigation in floral trait variation among populations may provide important information about the evolution, maintenance and/or loss of heterostyly.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that the morphological components of distyly can display some flexibility (Richards & Koptur 1993, Faivre & McDade 2001. Such studies took into consideration a great number of individuals from a number of populations and revealed that variation of floral traits associated with distyly may exhibit overlapping of values.…”
Section: Introductionmentioning
confidence: 99%
“…As espécies são consideradas heterostílicas quando os indivíduos podem ser divididos em duas classes morfológicas distintas (longistilas e brevistilas) com uma severa hercogamia recíproca entre os morfos (Faivre & McDade 2001). Com base nessas condições estruturais, a espécie apresentou características morfológicas de monomorfismo longistílico (Barrett 1992, Hamilton 1990) e "approach herkogamy" (disposição morfológica do complexo estigma-antera, com o estigma localizando-se sempre acima das anteras).…”
Section: Discussionunclassified
“…Rubiaceae contém o maior número de espécies distílicas dentre todas as famílias nas quais tal dimorfismo é conhecido, sendo encontrada em 416 espécies distribuídas em 91 gêneros (Ganders 1979, Barrett & Richards 1990, Passos & Sazima 1995. A ocorrência de variações na apresentação da distilia é comum na família, sendo demonstrada para espécies de Psychotria, Palicourea, Bouvardia e Guetarda (Sobrevila et al 1983, Hamilton 1990, Richards & Koptur 1993, Faivre & McDade 2001, Coelho & Barbosa 2003.…”
Section: Introductionunclassified
“…A heterostilia é bastante comum nos representantes estudados da família Rubiaceae, principalmente no gênero Psychotria (Hamilton 1990;Faivre & McDade 2001;Lau & Bosque 2003;Castro & Araújo 2004). Psychotria spectabilis apresentou diferenças na fecundidade entre os morfos florais, sendo esta maior nas flores brevistilas.…”
Section: Características Floraisunclassified